Proceedings of the 18th Annual Conference on Computer Graphics and Interactive Techniques 1991
DOI: 10.1145/122718.122727
|View full text |Cite
|
Sign up to set email alerts
|

Digital halftoning with space filling curves

Abstract: This paper introduces a new digital halftoning technique that uses space filling curves to generate aperiodic patterns of clustered dots. This method allows the parameterization of the size of pixel clusters. which can vary in one pixel steps. The algorithm unities, in this way, the dispersed and clustered-dot dithering techniques.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
53
0

Year Published

1997
1997
2022
2022

Publication Types

Select...
4
3
3

Relationship

0
10

Authors

Journals

citations
Cited by 81 publications
(53 citation statements)
references
References 11 publications
0
53
0
Order By: Relevance
“…They found that using an SFC, rather than the conventional raster scan, typically results in superior performance of the overall estimation process, especially in the presence of localized motion or other random outliers. Velho and Gomez (1991) propose a digital halftoning technique that uses SFCs to generate periodic patterns of clustered dots. Papamarkos and Atsalakis (2000) propose a graylevel reduction approach that uses both the image gray-levels and additional local spatial features.…”
Section: The Hilbert Space-filling Curve (Hc)mentioning
confidence: 99%
“…They found that using an SFC, rather than the conventional raster scan, typically results in superior performance of the overall estimation process, especially in the presence of localized motion or other random outliers. Velho and Gomez (1991) propose a digital halftoning technique that uses SFCs to generate periodic patterns of clustered dots. Papamarkos and Atsalakis (2000) propose a graylevel reduction approach that uses both the image gray-levels and additional local spatial features.…”
Section: The Hilbert Space-filling Curve (Hc)mentioning
confidence: 99%
“…The easiest way to take that decision can be placing the dots at the positions carrying higher intensity values in the cell but that fails to retain the gray appearance. Application of space-filling curve [11] for such decision has been reported and found to be able to generate significantly high quality half-tone images. In this paper, we consider the position decision as an optimization problem, where the optimized positions of white dots are obtained by minimizing the visual cost function ( φ ).Since, half-tone images aim to represent close approximation of original contone image the target can be minimizing the error between original contone and resulting half-tone image.…”
Section: Introductionmentioning
confidence: 99%
“…This curve has two features: (1) The curve walks always in her vertical or horizontal proximity, and (2) The curve walks on a random path. So, many dither methods have been proposed using Hilbert curve to combine the advantages of ordered dither and error diffusion [6], [7].…”
Section: Introductionmentioning
confidence: 99%